Sobre el buen uso de los monumentos arqueológicos - Bermejo Barrera, José Carlos (Gerión. Revista de Historia Antigua, 2002)
In this article the current situation of historical knowledge is studied by developing an analysis of the treatment of archaeological artifacts as the main point. Three are the main argumentation points treated: first, the transformation of archaeological artifact in merchandise; second, the integration of that archaeological artifact in the museum and exhibition industry, and, third, the banalitation of the artifact, that, at the end, becomes an object for touristic consume.